Micropollutant Control in Wastewater Treatment: A Review of Harnessing Nitrification and Denitrification Biotransformation of Micropollutant - Muhammad, Hanaa A.; Masyab, Hikmat M.; Othman, Bakhtyar A.; Mahmood, Yaseen N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Micropollutants, an array of organic compounds such as pharmaceuticals, personal care products, and agrochemicals, are pervasive in contemporary ecosystems, posing significant threats to environmental health even in trace concentrations. Therefore, exploring an efficient and effective technique to remediate these pollutants is essential. Nitrification–denitrification (ND) have emerged as one of the most sustainable treatment methods that effectively mitigate micropollutants while facilitating their biotransformation. This review provides a comprehensive analysis of the intricate interactions fundamentally and mechanically between the ND process and the influencing factors, such as dissolved oxygen (DO) concentration and pH optimization, which are vital to the success of micropollutant biotransformation. Insights gained from this examination contribute to a deeper understanding of microbial strategies, which offer potential avenues for sustainable environmental management and the protection of ecosystem integrity.